The sweetest thing: the influence of angularity, symmetry, and the number of elements on shape-valence and shape-taste matches - Salgado Montejo, Alejandro; Alvarado, Jorge A.; Velasco, Carlos; Salgado, Carlos J.; Hasse, Kendra; Spence, Charles (Frontiers in Psychology, 2015)
A within-participants experiment was conducted in two countries (the UK and Colombia) in order to investigate the matching of shapes to taste words. Comparing the two countries allowed us to explore some of the cultural differences that have been reported thus far solely in terms of people’s visual preferences. In particular, we addressed the question of whether properties other than angularity influence shape-valence and shape-taste matching (crossmodal correspondences). The participants in the present study repeatedly matched eight shapes, varying in terms of their angularity, symmetry, and number of elements to one of two words - pleasant or unpleasant and sweet or sour. Participants’ choices, as well as the latency of their responses, and their hand movements, were evaluated. The participants were more likely to judge those shapes that were rounder, symmetrical, and those shapes that had fewer elements as both pleasant and sweet. Those shapes that were more angular, asymmetrical, and that had a greater number of elements, were more likely to be judged as both unpleasant and sour instead. The evidence presented here therefore suggests that aside from angularity and roundness, both symmetry/asymmetry and the number of elements present in a shape also influence valence and taste categorizations.